2003
DOI: 10.1128/iai.71.1.575-579.2003
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Immunogenicity to Mycobacterium tuberculosis by Vaccination with an Alphavirus Plasmid Replicon Expressing Antigen 85A

Abstract: The immunogenicity of a plasmid DNA vaccine incorporating Sindbis virus RNA replicase functions (pSINCP) and expressing antigen 85A (Ag85A) from Mycobacterium tuberculosis was compared with a conventional plasmid DNA vector encoding Ag85A. pSINCP-85A was highly immunogenic in mice and gave enhanced long-term protection against M. tuberculosis compared with the conventional vector

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 19 publications
3
33
0
Order By: Relevance
“…Alternatively, multiple CpG motifs can be added to the DNA backbone to increase its adjuvant effects. Furthermore, the development of new DNA vaccines that incorporate the Sindbis virus RNA replicase increase the immunogenicity of conventional DNA vaccines and allow lower doses of DNA to be administered [100]. For example, Derrick et al found that a Sindbis virus-based DNA vaccine encoding the M. tuberculosis Ag85B was able to provide protection comparable to that of BCG based both on a reduction in CFU and a prolongation in survival [29].…”
Section: Dna Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, multiple CpG motifs can be added to the DNA backbone to increase its adjuvant effects. Furthermore, the development of new DNA vaccines that incorporate the Sindbis virus RNA replicase increase the immunogenicity of conventional DNA vaccines and allow lower doses of DNA to be administered [100]. For example, Derrick et al found that a Sindbis virus-based DNA vaccine encoding the M. tuberculosis Ag85B was able to provide protection comparable to that of BCG based both on a reduction in CFU and a prolongation in survival [29].…”
Section: Dna Vaccinationmentioning
confidence: 99%
“…Vaccination with plasmid DNA encoding 72F elicits a robust CTL response against Mtb32 [93][94][95][96][97][98][99][100][101][102] and generates protective immunity in both mice and guinea pigs [87]. Interestingly, when the vaccine is formulated as a polyprotein vaccine, it elicits a strong CTL response against Mtb32 [93][94][95][96][97][98][99][100][101][102] , an epitope that elicits CD8 + T cells after DNA vaccination. A critical variable appears to be the adjuvant -and the adjuvant AS01B seems to be particularly effective at stimulating a CD8 + T cell response.…”
Section: Subunit Vaccinesmentioning
confidence: 99%
“…To enhance the immunogenicty of genetic immunization, other vectors expressing M. tuberculosis antigens have been tested, such as alphavirus [62,63], adenovirus [64], or vaccinia virus [65]. The use of these viral-based vectors is under consideration in prime-boosting strategies to enhance an antigen-specific immune response.…”
Section: Dna Vaccinesmentioning
confidence: 99%
“…Several groups have demonstrated the ability of suicidal DNA vaccines to induce high-level humoral and cellmediated immunity against a variety of antigens, with immunized animals developing more prominent immune responses than those receiving a conventional DNA vaccine encoding the same antigen (Berglund et al, 1998;Deshpande et al, 2002;Hariharan et al, 1998;Kirman et al, 2003;Leitner et al, 2000). In addition, it has been demonstrated that suicidal DNA vaccines could break immunological tolerance by activating innate antiviral pathways, in contrast to conventional DNA vaccines encoding the same antigen (Leitner et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The RNA selfamplifying property is of considerable interest with respect to vaccine biosafety: the vector replicates at the RNA level and not at the DNA level, so the rate of foreign DNA present in vivo and possessing 'genome integration potential' is controlled and does not increase following vaccination (contrary to some attenuated or recombinant vaccines). Furthermore, when a suicidal DNA vaccine is transfected into cells, it leads eventually to apoptosis of the transfected cells (Kohno et al, 1998;Leitner et al, 2000), which is particularly important in alleviating the concerns of potential integration and cell transformation generated by the use of conventional DNA vaccines (Gurunathan et al, 2000;Lewis & Babiuk, 1999).Several groups have demonstrated the ability of suicidal DNA vaccines to induce high-level humoral and cellmediated immunity against a variety of antigens, with immunized animals developing more prominent immune responses than those receiving a conventional DNA vaccine encoding the same antigen (Berglund et al, 1998;Deshpande et al, 2002;Hariharan et al, 1998;Kirman et al, 2003;Leitner et al, 2000). In addition, it has been demonstrated that suicidal DNA vaccines could break immunological tolerance by activating innate antiviral pathways, in contrast to conventional DNA vaccines encoding the same antigen (Leitner et al, 2003).…”
mentioning
confidence: 99%